Analysis of thickness in deck slab overhangs (Research, Society and Development, 2021)
The reinforced concrete highway bridges must be built taking into account the action of permanent and variable loads, as well as the dynamic actions from vehicle traffic. The advent of globalization and consequently the expansion of vehicle flow, especially large vehicles, are some of the factors of extreme importance to be evaluated in the process of assembly and design of superstructures, because they are inherent to the emergence of transverse bending moments in the bridge slab.  The correct consideration of these aspects for the structural analysis of a bridge motivated the development of this study to evaluate the stresses aroused in the structural element responsible for supporting traffic loads, the slabs. Intrinsic to this study is the analysis of the relationship between the variation in thickness of the cantilever slabs and the intensity of the transverse moments aroused in the region of influence of the deck. The study approaches the analytical model developed by Bakht and Jaeger (1985), performing an inspection of the bending moments aroused in the cantilever slab, from the application of concentrated loads on the cantilever surface, as well as the variation of their positions and the thicknesses of the superstructure. The research is carried out with the aid of the Microsoft Excel computer program. The conclusions of this work deal with the correct analysis of the efforts aroused in cantilever bridge slabs, as well as the benefits provided by varying the thickness of the deck and the introduction of edge beams in the structure, providing greater efficiency in reducing the transverse moments aroused in the deck.